Recent innovations in artificial skin. (10th December 2019) - Low, Zhi Wei Kenny; Li, Zibiao; Owh, Cally; Chee, Pei Lin; Ye, Enyi; Dan, Kai; Chan, Siew Yin; Young, David James; Loh, Xian Jun
Abstract : Efforts to replicate skin have resulted in remarkable developments in soft materials, flexible devices and tissue engineering. In this review, the properties of natural skin are discussed and compared with the performances of current artificial skins. Abstract : The skin is a "smart", multifunctional organ that is protective, self-healing and capable of sensing and many forms of artificial skins have been developed with properties and functionalities approximating those of natural skin. Starting from specific commercial products for the treatment of burns, progress in two fields of research has since allowed these remarkable materials to be viable skin replacements for a wide range of dermatological conditions. This review maps out the development of bioengineered skin replacements and synthetic skin substitutes, including electronic skins. The specific behaviors of these skins are highlighted, and the performances of both types of artificial skins are evaluated against this. Moving beyond mere replication, highly advanced artificial skin materials are also identified as potential augmented skins that can be used as flexible electronics for health-care monitoring and other applications.